ON THE STATUS OF CODACOND IN PHONOLOGY - Beckman, Jill N. (International Journal of English Studies, 2009)
Onset/coda feature licensing asyrnmetries have been extensively studied in the generative phonological literature. Pre-Optimality Theory analyses of such asymmetries rely on positional licensing or positional rnarkedness statements, ofwhich Ito’s (1986,1989) Coda Conditionis the best-known. In OT, a different approach to onsetlcoda asyrnmetries has emerged: onset-specific faithfulness (Padgett 1995; Beckman 1999; Lombardi 1999,2001). In a recent paper, Lombardi (2001) argues that both onset faithfulness and the Coda Condition are required to account for the range of repairs associated with coda/onset asymrnetries in the licensing of place features, arguing that positional faithfulness alone cannot generate epenthesis as a repair strategy. In this paper, I show, through analyses of Tamil and Axininca Carnpa, that the Coda Condition is not required to generate place-driven epenthesis; rather, epenthesis emerges from the interaction of onset faithfulness with other, independently motivated faithfulness and syllable well-formedness constraints.